Poor neighbourhood conditions and low belongingness to community is associated with poor mental health among immigrants - Khan, Tasneem; Cooke, Martin (My University, 2024)
Limited research exists about how neighbourhood or household characteristics might be related to mental health among immigrants in Canada. This study examined immigrants’ exposure to potentially unfavourable aspects of their households and neighbourhoods and how these factors were associated with mental health. Immigrants living in neighborhoods with higher situational vulnerability (e.g., higher proportions of people without high school diploma, more dwellings in need of repairs) were more likely to have poor self-rated mental health. Immigrants with a weak sense of belonging to their communities had four times higher odds of poor self-rated mental health than those with a stronger sense of belonging.
Keywords: Environment; Health; Immigration & ethnocultural diversity; Population & demography